The Effect of Phubbing on the Decrease in the Value of Student Social Solidarity in the Millennial Era (An Environment Because It Focuses More on Gadgets) - Adripen Adripen; Cut Afrina (Jurnal Mamangan, 2022)
The purpose of this study was to determine the effect of phubbing on the decline in the value of student social solidarity in the millennial era (an environment because it is more focused on gadgets) in library and information science students at UIN Ar-Raniry Banda Aceh. This research uses quantitative research methods. The research variable consists of one independent variable, namely: Phubbbing (X) and the binding variable, namely: a decrease in the value of student Social Solidarity in the Millennial era (Y). The sampling technique used was technique sampling with a total of 111 students, while the samples were 87 students. Based on the results of the descriptive analysis test using the mean formula and the results of the derivative of the grand mean of the variable (X), it is categorized well with a mean value of 3.2. While the variable (Y) is categorized as good with an average value of 2.89. The result of the product moment correlation test, that the large correlation coefficient between variable (X) and variable (Y) obtained a result of 0.711, the coefficient interval between 0.80-1000 shows a very strong influence, where the direction of the influence is positive because the R value shows a number positive. The simple regression results for variable (X) and variable (Y) Y = 10.553 + 0, 802X and R Square for 0.711 means that the effect of variable (X) with variable (Y) is 52.20%. Other factors outside this study amounted to 48.80%.